Rapid polygenic response to secondary contact in a hybrid species. Issue 1853 (26th April 2017) - Sætre, Glenn-Peter; Cuevas, Angélica; Hermansen, Jo S.; Elgvin, Tore O.; Fernández, Laura Piñeiro; Sæther, Stein A.; Cascio Sætre, Camilla Lo; Eroukhmanoff, Fabrice
Abstract : Secondary contact between closely related species can have genetic consequences. Competition for essential resources may lead to divergence in heritable traits that reduces interspecific competition leading to increased rate of genetic divergence. Conversely, hybridization and backcrossing can lead to genetic convergence. Here, we study a population of a hybrid species, the Italian sparrow ( Passer italiae ), before and after it came into secondary contact with one of its parent species, the Spanish sparrow ( P. hispaniolensis ), in 2013. We demonstrate strong consequences of interspecific competition: Italian sparrows were kept away from a popular feeding site by its parent species, resulting in poorer body condition and a significant drop in population size. Although no significant morphological change could be detected, after only 3 years of sympatry, the Italian sparrows had diverged significantly from the Spanish sparrows across a set of 81 protein-coding genes. These temporal genetic changes are mirrored by genetic divergence observed in older sympatric Italian sparrow populations within the same area of contact. Compared with microallopatric birds, sympatric ones are genetically more diverged from Spanish sparrows. Six significant outlier genes in the temporal and spatial comparison (i.e. showing the greatest displacement) have all been found to be associated with learning and neural development in other bird species.